Decorative board - IWASAKI ATSUSHI; YASUI MASATAKA; SUZUKI KOSHI; YOKOI AKITOMO (2010)
Disclosed is a decorative board comprising a core layer and a decorative layer. The core layer is composed of a prepreg which is impregnated with a slurry containing (a) an organic resin component containing a phenyl-formaldehyde resin and an amino-formaldehyde resin, (b) one or more substances selected form the group consisting of carbonates, silica, talc and fly ash, and (c) a metal hydroxide.